2022
DOI: 10.3847/1538-4357/ac5f54
|View full text |Cite
|
Sign up to set email alerts
|

The Curious Case of ASASSN-20hx: A Slowly Evolving, UV- and X-Ray-Luminous, Ambiguous Nuclear Transient

Abstract: We present observations of ASASSN-20hx, a nearby ambiguous nuclear transient (ANT) discovered in NGC 6297 by the All-Sky Automated Survey for Supernovae (ASAS-SN). We observed ASASSN-20hx from −30 to 275 days relative to the peak UV/optical emission using high-cadence, multiwavelength spectroscopy and photometry. From Transiting Exoplanet Survey Satellite data, we determine that the ANT began to brighten on 2020 June 22.8 with a linear rise in flux for at least the first week. ASASSN-20hx peaked in the UV/opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 190 publications
0
7
0
Order By: Relevance
“…In addition to studying supernovae (SNe; e.g., Bose et al 2018Bose et al , 2019Hoeflich et al 2021;Chen et al 2022), ASAS-SN obtains data for a broad range of transients, multi-messenger searches, and variable sources. For transients, these include tidal disruption events (TDEs; e.g., Holoien et al 2019b,c, 2020, Hinkle et al 2021, Payne et al 2022, novae (e.g., Kawash et al 2021bKawash et al , 2022, dwarf novae (e.g., Kawash et al 2021a), and changing look or other active galactic nuclei (AGN; e.g., Neustadt et al 2020, Hinkle et al 2022, Holoien et al 2022. There are multi-messenger searches associated with both neutrino (e.g., IceCube Collaboration et al 2018, Necker et al 2022) and gravitational wave (e.g., de Jaeger et al 2022) events.…”
mentioning
confidence: 99%
“…In addition to studying supernovae (SNe; e.g., Bose et al 2018Bose et al , 2019Hoeflich et al 2021;Chen et al 2022), ASAS-SN obtains data for a broad range of transients, multi-messenger searches, and variable sources. For transients, these include tidal disruption events (TDEs; e.g., Holoien et al 2019b,c, 2020, Hinkle et al 2021, Payne et al 2022, novae (e.g., Kawash et al 2021bKawash et al , 2022, dwarf novae (e.g., Kawash et al 2021a), and changing look or other active galactic nuclei (AGN; e.g., Neustadt et al 2020, Hinkle et al 2022, Holoien et al 2022. There are multi-messenger searches associated with both neutrino (e.g., IceCube Collaboration et al 2018, Necker et al 2022) and gravitational wave (e.g., de Jaeger et al 2022) events.…”
mentioning
confidence: 99%
“…These energetic events are predicted to have high event-rate densities in AGN disks and may contribute a considerable fraction of the diffuse neutrino background. Recently, a few potential AGN disk transients were detected although their origins were still unclear (Hinkle et al 2022;Holoien et al 2022), and more AGN disk transients might be recorded in previous optical survey projects. Lightcurves of AGN disk transients could have similar peak brightness, peak time, and evolution pattern with those of TDEs (Zhu et al 2021d;Grishin et al 2021;Ren et al 2022) so that some AGN disk transients could be wrongly identified as TDEs.…”
Section: Discussionmentioning
confidence: 99%
“…With its large field of view, TESS observes a large number of bright SNe, averaging six type Ia SN light curves for every sector. TESS has also made important contributions to extragalactic transient studies more broadly: Vallely et al (2021) used TESS data to measure rise times of 22 core-collapse SNe from 2018-2020, while high-cadence TESS light curves have enabled new investigations of tidal disruption events (Holoien et al 2019), gamma-ray bursts (Smith et al 2021), and active galactic nuclei (Burke et al 2020;Weaver et al 2020;Payne et al 2021;Hinkle et al 2022;Payne et al 2022;Hinkle et al 2023).…”
Section: Introductionmentioning
confidence: 99%